The Philippine islands, 1493-1803 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the beginning of the nineteenth century, Vol. XLIV, 1700-1736 - Blair, Emma Helen 1911; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908.; Libtech/IgLibrary. ([Cleveland, Ohio A.H. Clark Co., 1906])
Explorations by Early Navigators, Descriptions of the Islands and their Peoples, their History and Records of the Catholic Missions, as related in Contemporaneous Books and Manuscripts, showing the Political, Economic, Commercial and Religious Conditions of those Islands from their earliest relations with European Nations to the close of the Nineteenth Century.
Translated from original.
Electronic Reproduction.
Keywords: Demarcation line of Alexander VI; Missions -- Philippines; Electronic books; Philippines -- History -- Sources; Philippines -- Discoveries and explorations